PsycEXTRA Dataset 2003
DOI: 10.1037/e427992008-001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between schedule type and ACT Assessment scores: A longitudinal study

Abstract: This study investigated trends in the mean ACT Assessment scores of 450 public high schools in Illinois and Iowa, according to how they scheduled classes. The schools continuously employed either a traditional eight-period daily schedule, 4 x 4 semester schedule, or an eight-block alternating day block schedule. Seven years of data were available for the blocked schools, representing 2 years preimplementation through 4 years postimplementation. The eight-period schools demonstrated a slight upward trend in mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In contrast to the lack of research understanding district factors and student performance, there has been a great deal of research on the relationship between school related factors and student achievement. The research has pointed to the influence of student wealth, race, school size, curriculum, teacher preparation, and other variables that were found to predict a reasonable degree of student outcomes [6][7][8][9][10]. For example, Ma and Klinger, in their study of New Brunswick Schools, found that how student and school factors influenced achievement varied over the type of academics examined such that race, gender, and wealth of students is seen as significant predictors of performance.…”
mentioning
confidence: 99%
“…In contrast to the lack of research understanding district factors and student performance, there has been a great deal of research on the relationship between school related factors and student achievement. The research has pointed to the influence of student wealth, race, school size, curriculum, teacher preparation, and other variables that were found to predict a reasonable degree of student outcomes [6][7][8][9][10]. For example, Ma and Klinger, in their study of New Brunswick Schools, found that how student and school factors influenced achievement varied over the type of academics examined such that race, gender, and wealth of students is seen as significant predictors of performance.…”
mentioning
confidence: 99%
“…In 1997, Skrobarcek reported high school students taking Algebra I in a block schedule had a higher rate of failure than those on a traditional schedule (Lawrence & McPherson, 2000). Problems with block scheduling may be due to transition time, stress at the beginning of the implementation process and difficulty for teachers to adapt (Harmston, Pliska, Ziomeck & Hackman, 2003;Spencer & Lowe, 1994).…”
Section: Literature Review/theoretical Frameworkmentioning
confidence: 99%